2020
DOI: 10.3390/metabo11010023
|View full text |Cite
|
Sign up to set email alerts
|

Total vs. Bioavailable: Determining a Better 25(OH)D Index in Association with Bone Density and Muscle Mass in Postmenopausal Women

Abstract: The concurrent presence of low bone density (osteopenia/osteoporosis) and low muscle mass (sarcopenia) in older adults has led to the recognition of “osteosarcopenia” (OS) as a singular entity. Vitamin D may play important role in the manifestation of OS, in terms of intake, absorption, and bioavailability. Evidence suggests that bioavailable 25(OH)D may be a better indicator of Vitamin D compared to total 25(OH)D due to its weak bind to albumin, increasing its ‘availability’. The aim of this study was to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 72 publications
0
8
0
1
Order By: Relevance
“…Most of routinely used vitamin D assays do not distinguish between the DBP-bound 25(OH)D, albumin-bound 25(OH)D and free biologically active vitamin D. Free 25(OH)D can be calculated or analyzed directly [6]. Free 25(OH)D includes only unbound 25(OH)D, whereas bioavailable 25(OH)D comprises free 25(OH)D and albumin-bound 25(OH)D [19]. Liver disease, kidney disease, and conditions such as pregnancy, genetic polymorphisms, and menopause affect DBP or albumin synthesis [6].…”
Section: Introductionmentioning
confidence: 99%
“…Most of routinely used vitamin D assays do not distinguish between the DBP-bound 25(OH)D, albumin-bound 25(OH)D and free biologically active vitamin D. Free 25(OH)D can be calculated or analyzed directly [6]. Free 25(OH)D includes only unbound 25(OH)D, whereas bioavailable 25(OH)D comprises free 25(OH)D and albumin-bound 25(OH)D [19]. Liver disease, kidney disease, and conditions such as pregnancy, genetic polymorphisms, and menopause affect DBP or albumin synthesis [6].…”
Section: Introductionmentioning
confidence: 99%
“…The total MRS score was calculated by summation of all subscales yielding a score range from 0 to 44. Then, the severity of symptoms was classified as none/little (0-4), mild (5-8), moderate (9)(10)(11)(12)(13)(14)(15)(16), and severe/very severe (17 or more). The scale had good reliability (Cronbach's alpha = 0.880) in our target population.…”
Section: Data Collectionmentioning
confidence: 99%
“…One of the factors that have recently been a matter of concern is the 1 2 perceived social support among females. Research highlights that women need social support to cope and adapt to the menopausal symptoms in this stressful period of their life, and this may help control their symptoms [11,12]. The severity of symptoms may have a negative impact on daily activity and quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been suggested that the estimates of free and bioavailable VitD may have better correlation with BMD [18,38]. A study in postmenopausal women showed an association between free and bioavailable VitD with hip and total body BMD only in women not taking calcium or VitD supplements [18].…”
Section: Discussionmentioning
confidence: 99%